THE EFFECT OF THE INDEPENDENT LEARNING CURRICULUM, SELF-EFFICACY, STUDENTS LEARNING STYLES, PEERS, AND LEARNING FACILITIES ON STUDENTS LEARNING ACHIEVEMENT IN ECONOMICS SUBJECT IN GRADE XI PHASE F AT SMA N 2 LUBUK SIKAPING - Derusman, Riyan; Jimi Ronald; Dina Amaluis (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze: 1) The effect of the Merdeka Belajar Curriculum on learning achievement, 2) The effect of self-efficacy on learning achievement, 3) The effect of students' learning styles on learning achievement, 4) The effect of learning peers on learning achievement, 5) The effect of learning facilities on learning achievement. The type of research used in this study is associative/quantitative research. The research was conducted in July 2025. The population in this study was all 11th grade students in economics at SMAN 2 Lubuk Sikaping. The sample in this study consisted of 80 people. The sampling technique used was random sampling, and the data analysis techniques used were descriptive analysis and inductive analysis, with the help of Eviews and SPSS version 21.0. The results of the study indicate that there is a significant influence between the Merdeka Belajar Curriculum and academic achievement. This can be seen from the calculated t-value of -3.640 < the table t-value of 1.992, while the significance value is 0.000 < 0.005, meaning that the Merdeka Belajar Curriculum has a significant influence on students' academic achievement. X2 shows that the calculated t-value is 2.064 > the table t-value of 1.992, while the significance value is 0.0043 > 0.005, meaning that self-efficacy has a significant effect on academic achievement. The research results show a significant influence between X3 learning style and academic achievement, as seen in the calculated t-value of 2.074 > t-table value of 1.992, while the significance value is 0.0042 > 0.005, meaning that learning style has a significant influence on academic achievement. Based on the research results, there is a significant influence between learning style and academic achievement of students in class XI F at SMAN 2 Lubuk Sikaping. This can be seen from the calculated t-value of -7.132 < t-table value of 1.992, while the significance level is 0.001 < 0.005, meaning that X4 peer influence significantly affects academic achievement. There is a significant influence between X5 learning facilities and the academic achievement of students in class XI F at SMAN 2 Lubuk Sikaping. This can be seen from the calculated t-value of 3.611 < t-table value of 1.992, while the significance value is 0.00 < 0.005, meaning that learning facilities significantly influence academic achievement.